Who Is Influencing Whom? Latino Parent–Child Request Interactions and Product Purchases in Food Retail Environments - Castro, Iana A. (Soc Mar Q, 2017)
This study examines Latino parent–child interactions about foods and beverages requested in food retail environments in San Diego, CA. It seeks to extend our understanding of parent–child request interactions and purchases by studying how the number of product request interactions and purchases differ based on four factors that have been understudied in previous parent–child interaction research: parent gender, child gender, product healthfulness, and who initiated the request interaction (parent or child). By unobtrusively observing Latino parent–child dyads for the duration of a brief shopping trip, we found that parent and child gender are related to the number of request interactions initiated by parents and children. For gender-specific child-initiated request interactions, sons initiated more request interactions with fathers while daughters initiated more request interactions with mothers. Most request interactions were for products that were categorized as calorie dense, and a higher percentage of these products were purchased as a result of parent-initiated (vs. child-initiated) request interactions. The results provide important considerations for practitioners and researchers working on improving nutrition and reducing obesity. Assumptions about who is influencing whom in food store request interactions are challenged, requiring more research.